The historical contributions of Islamic civilization in medical and applied sciences: A survey from the Muslims product - Tahir, Abdurrahman; Abubakar Abdul hakim, Abdullah; kabara Auwal, Halabi (2015)
Islamic medicine is this developed during the period of Islamic civilization which, spanned for about seven or eight centuries with the rise of Islam in the Arabian Peninsula in the seventh century till the fall of the Islamic empire in the Middle East and Spain in the fourteenth century. This study will highlight a history and considerable achievements of Muslims scholars in medical and applied sciences, which commenced with a special outlook of the gigantic contribution of the ‘prophetic medicine’ (Tibb Al-Nabawiy), then a significant contributions of Ibn sina (965-1045), Al haytham (965-1040), Alzahrawi (936-1013) then Al-razi (864-930) and Al-khwarizmi (780-850AD respectively. It is also the vision of this study to show the beauty of Islam and Islamic intellectualism in recounting it’s achievement in the diverse areas of medicine, pharmacy, earth sciences, mathematics and geometry. In the cause of gathering and analysing this information, the study is suitably adapted exploratory survey, and content analysis approach for the qualitative study. This paper is also envisioned to call and reorients the Muslims minds for search and research on Islamic products and its relevance to the contemporary sciences.